Preparation method of self-carbonized recycled aggregate concrete

By using NaHCO3 microcapsules and alkali treatment technology wrapped in sodium bicarbonate in recycled concrete, the problems of uneven reactions and crystallization of carbonization products in the liquid-solid carbonization method are solved, and an efficient and uniform carbonization process under normal pressure is achieved. The mechanical properties and durability of concrete are significantly improved.

CN119118577APending Publication Date: 2024-12-13PUTIAN UNIV +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411127500.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing liquid-solid carbonization method causes local reactions to be over-fast or excessive in recycled concrete, affecting the consistency of mechanical properties, and requires strict control of pressure and gas concentration, which is complicated to operate, and the traditional method has the problem of carbonization product crystallization during efficient carbonization. , affects performance.

Method used

By mixing sodium bicarbonate powder with polylactic acid solution, NaHCO3 microcapsules are formed and evenly mixed with cement and mineral blends under normal pressure, fine aggregates are regenerated with alkali treatment to form gelling materials containing carbon sources. Gradually release the carbon source to improve carbonization uniformity and density.

Benefits of technology

It significantly improves the density and mechanical properties of concrete, reduces the construction cycle, is suitable for large-scale production, and avoids the adverse effects of carbonized product crystallization on performance, and improves the strength and durability of the interface transition zone.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of self-carbonized recycled aggregate concrete. The preparation method comprises the following steps: adding polylactic acid into an ethyl acetate solvent, dissolving, and mixing to form a polylactic acid solution; dispersing and adding sodium bicarbonate powder into the polylactic acid solution, and stirring, so that sodium bicarbonate is uniformly distributed in the polylactic acid solution; adding the polylactic acid solution in which sodium bicarbonate is uniformly distributed into a water phase containing a surfactant, stirring at a high speed, and emulsifying to form an O / W emulsion; the O / W emulsion is subjected to solvent volatilization under stirring, so that polylactic acid is cured, and microcapsules wrapping sodium bicarbonate are formed; after centrifuging, filtering and settling, separating and collecting the formed sodium bicarbonate microcapsules, washing and drying; uniformly mixing the sodium bicarbonate microcapsules, the cement and the mineral admixture to obtain a cementing material; and providing the recycled fine aggregate to prepare the self-carbonized recycled aggregate concrete. The preparation method disclosed by the invention is simple, short in period and low in cost, and has a relatively good market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resource utilization of construction waste, and in particular to a method for preparing self-carbonized recycled aggregate concrete. Background Art

[0002] With the rapid advancement of urbanization, natural aggregates are becoming increasingly scarce, and recycled concrete aggregates (RCAs) obtained by crushing and screening waste concrete have become a viable alternative. However, the direct use of untreated RCAs to prepare new concrete, especially under high replacement rates, has poor mechanical and durability properties due to the presence of a large amount of old mortar inside or on the surface of RCAs. Therefore, RCAs need to be modified before application. At present, accelerated carbonation is one of the more economical solutions to improve the quality of RCAs and in line with the concept of sustainable development. It introduces CO2 into the residual cement slurry to react with the hydration product to generate calcium carbonate and additional amorphous CSH gel, thereby improving the compactness of the recycled aggregate and the interface transition zone, and thus enhancing the mechanical and durability properties of recycled aggregate concrete.

[0003] At present, commonly used accelerated carbonization methods generally include gas-solid and liquid-solid.

[0004] Among them, the gas-solid method accelerates carbonization by increasing the CO2 concentration, pressure, temperature and reasonable relative humidity (RH); however, due to the relatively low permeability of CO2 gas in recycled aggregates, the carbonization time is at least 7 days; if pure CO2 (>99.5%) or mixed gas is injected from one side of the reaction chamber and discharged from the other side, the curing time of recycled concrete can be greatly reduced to less than 96h. The other liquid-solid accelerated carbonization method is more effective and rapid in improving the carbonization efficiency of recycled concrete, because the carbonization reaction between the hydration product and the water-CO2 mixture is more complete than the carbonization reaction in CO2 gas. Continuously bubbling pure CO2 or mixed CO2 and N2 gas in a solution containing recycled concrete fine particles significantly increases the carbonization reaction degree of cement paste to more than 90% within only 6h. Therefore, the liquid-solid carbonization method is much faster than the gas-solid carbonization method.

[0005] However, research results show that the liquid-solid carbonization method can cause local reactions to be too fast or excessive, resulting in uneven reactions, which in turn affects the consistency of mechanical properties. The pressure and gas concentration also need to be strictly controlled during the reaction, and the high-pressure equipment used in the reaction is demanding and the operation is relatively complicated. Summary of the invention

[0006] The present invention provides a method for preparing self-carbonized recycled aggregate concrete, aiming to improve at least one of the above technical problems.

[0007] In order to solve the above technical problems, the present invention provides a method for preparing self-carbonized recycled aggregate concrete, comprising the following steps:

[0008] Step S1: adding polylactic acid into ethyl acetate solvent to dissolve and mix to form a polylactic acid solution;

[0009] Step S2: dispersing sodium bicarbonate powder into the polylactic acid solution under magnetic stirring, and stirring for 1 to 2 hours to make the sodium bicarbonate evenly distributed in the polylactic acid solution;

[0010] Step S3: adding the polylactic acid solution containing sodium bicarbonate evenly distributed into the aqueous phase containing the surfactant, and emulsifying for 0.5 to 2 hours by high-speed stirring at 3000-10000 rpm to form an O / W emulsion;

[0011] Step S4: volatilizing the solvent of the O / W emulsion under stirring to solidify the polylactic acid to form microcapsules encapsulating the sodium bicarbonate;

[0012] Step S5: separating and collecting the formed sodium bicarbonate microcapsules after centrifugation, filtration and sedimentation, and then storing them after washing and drying;

[0013] Step S6: uniformly mixing the sodium bicarbonate microcapsules, cement and mineral admixtures to obtain a cementitious material containing a carbon source;

[0014] Step S7: providing recycled fine aggregate, with a water-cement ratio of 0.35 to 0.55 and a cementitious material containing a carbon source of 300 to 600 kg / m3, and preparing self-carbonized recycled aggregate concrete after stirring, vibrating and curing.

[0015] Preferably, in step S1, the concentration of the polylactic acid solution is 2-5%.

[0016] Preferably, in step S3, the aqueous phase contains 2% to 10% of a surfactant.

[0017] Preferably, in step S3, the surfactant is polyethylene glycol.

[0018] Preferably, in step S4, when the solvent is volatilized, the solvent volatilization process is accelerated by rotary evaporation, the duration is 2 to 6 hours, and the temperature is set to 50°C.

[0019] Preferably, in step S4, when the solvent is volatilized, the solvent volatilization process is accelerated by reduced pressure evaporation, the duration is 2 to 6 hours, and the temperature is set to 50°C.

[0020] Preferably, step S6 comprises:

[0021] Step S61, uniformly mixing the sodium bicarbonate microcapsules with cement in an amount of 5-10 wt.% of cement for 10-15 minutes;

[0022] Step S62, adding mineral admixtures and mixing to form a cementitious material containing a carbon source.

[0023] Preferably, in step S7, the provided recycled fine aggregate needs to be treated with alkali in advance by soaking in a sodium hydroxide solution with a concentration of 1-2% for 0.5 to 1 hour. After soaking, the recycled fine aggregate is rinsed with a large amount of clean water to remove residual alkali solution, and then the recycled fine aggregate is dried in the sun or in a low-temperature oven to ensure that no moisture remains.

[0024] Compared with the prior art, this embodiment has at least the following advantages:

[0025] 1. Under normal pressure conditions, by introducing NaHCO3 microcapsules that can evenly release carbon dioxide, the density and mechanical properties of concrete are improved by improving the uniformity of the carbonization process, and the compressive strength is significantly improved. This method does not require complex equipment and multi-step processing, has a simple process, reduces the construction cycle, is suitable for large-scale production, and has good market application prospects.

[0026] 2. The pore size distribution of recycled aggregate concrete prepared by this method is better than that of the traditional liquid-solid carbonization treatment method. Specifically, the average pore size is significantly reduced (from 46nm to 23nm), and the total porosity is significantly reduced (from 20% to 15.8% to 17.6%), indicating that the microstructure is more compact; the pore size distribution is more uniform, and the number of tiny pores increases, which helps to improve the mechanical and durability properties of concrete.

[0027] 3. Alkali treatment removes part of the old mortar, which can further enhance the bonding between the new cement paste and the recycled aggregate and improve the strength of the interface transition zone (ITZ). The alkali solution dissolves impurities and hydration products in part of the old mortar, increasing the ion content in the pore solution and providing more active sites, which is conducive to increasing the chemical bonding and mechanical bite force between it and the new cement paste, thereby improving the overall performance of the interface transition zone. The nanoindentation test results show that the interface transition zone of the recycled aggregate concrete prepared by this method has higher hardness and elastic modulus.

[0028] 4. Using NaHCO3 microcapsules as the internal carbon source of recycled aggregate concrete, in which sodium bicarbonate is wrapped by the shell, can avoid the problem of carbonization products directly crystallizing on the aggregate surface. The microcapsules gradually release the carbon source, reducing the adverse effects of the crystallization of carbonization products on the performance of recycled aggregates and the interface transition zone between recycled aggregates and new slurry. Because the direct use of sodium bicarbonate solution environment to carry out the liquid-solid carbonization process easily causes the carbonization products to crystallize on the aggregate surface, forming an uneven crystal layer, and the crystal layer will hinder the carbonization reaction deeper in the recycled aggregate, resulting in reduced carbonization efficiency. In addition, the coating effect of the microcapsule and the carbon source release rate can be flexibly adjusted, such as controlling its anti-rupture ability by adjusting the thickness of the microcapsule shell; controlling the crosslinking degree of the shell and thus controlling its stability by adjusting the amount of crosslinking agent and the crosslinking time. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] The embodiment of the present invention provides a method for preparing self-carbonized recycled aggregate concrete, comprising the following steps:

[0031] Step S1: adding polylactic acid into ethyl acetate solvent to dissolve and mix to form a polylactic acid solution; preferably, in step S1 of this embodiment, the concentration of the polylactic acid solution is 2-5%.

[0032] Step S2: dispersing sodium bicarbonate powder into the polylactic acid solution under magnetic stirring, and stirring for 1 to 2 hours to make the sodium bicarbonate evenly distributed in the polylactic acid solution;

[0033] Step S3: adding the polylactic acid solution with evenly distributed sodium bicarbonate to the aqueous phase containing a surfactant, and emulsifying for 0.5 to 2 hours by high-speed stirring at 3000-10000 rpm to form an O / W (oil-in-water) emulsion; wherein the aqueous phase contains 2% to 10% of a surfactant, and the surfactant helps to stabilize the microcapsules in the emulsion.

[0034] Preferably, in this embodiment, the surfactant is polyethylene glycol.

[0035] Step S4: volatilizing the solvent of the O / W emulsion under mechanical stirring at a speed of 100-500 rpm, so as to solidify the polylactic acid and form microcapsules encapsulating the sodium bicarbonate.

[0036] Preferably, in step S4, when the solvent is volatilized, rotary evaporation or reduced pressure evaporation is performed to accelerate the solvent volatilization process, the duration is 2 to 6 hours, and the temperature is set to 50°C.

[0037] Step S5: After centrifugation, filtration and sedimentation, the formed sodium bicarbonate microcapsules are separated and collected, and then stored after washing and drying for use in preparing self-carbonized recycled aggregate concrete.

[0038] Step S6: uniformly mixing the sodium bicarbonate microcapsules, cement and mineral admixtures to obtain a cementitious material containing a carbon source;

[0039] Specifically, in this embodiment, step S6 includes:

[0040] Step S61, uniformly mixing the sodium bicarbonate microcapsules with cement in an amount of 5-10 wt.% of cement for 10-15 minutes;

[0041] Step S62, adding mineral admixtures and mixing to form a cementitious material containing a carbon source. The mineral admixtures can be conventionally mixed, and no further details are given here.

[0042] Step S7: providing recycled fine aggregate, with a water-cement ratio of 0.35 to 0.55 and a carbon source-containing cementitious material dosage of 300 to 600 kg / m3, and finally preparing self-carbonized recycled aggregate concrete through mixing, vibrating and curing according to the standard concrete preparation process.

[0043] Specifically, in step S7, the provided recycled fine aggregate needs to be treated with alkali in advance by soaking in a sodium hydroxide solution with a concentration of 1-2% for 0.5 to 1 hour. After soaking, the recycled fine aggregate is rinsed with a large amount of clean water to remove residual alkali solution, and then the recycled fine aggregate is dried in the sun or in a low-temperature oven to ensure that no moisture remains.

[0044] Preferably, when preparing concrete using the embodiments of the present invention, the recycled fine aggregate can replace 50% to 100% of the natural fine aggregate.

[0045] The embodiment of the present invention further provides a self-carbonizing recycled aggregate concrete, which is prepared by the above-mentioned preparation method.

[0046] Compared with the prior art, this embodiment has at least the following advantages:

[0047] 1. Under normal pressure, by introducing NaHCO3 microcapsules that can evenly release carbon dioxide, the density and mechanical properties of concrete are improved by improving the uniformity of the carbonization process. Compared with uncarbonized recycled aggregate concrete, the 28-day compressive strength is increased by 26.36%, and compared with the traditional liquid-solid carbonization method, this method does not require complex equipment and multi-step processing, the process is simple, the construction cycle is reduced, and it is suitable for large-scale production. Because the liquid-solid carbonization method (such as impregnation with sodium bicarbonate solution) has high requirements for environmental control, it is easily affected by external conditions during the reaction process, and it is difficult to maintain a stable reaction environment. Improper environmental control may lead to incomplete reaction or low carbonization efficiency.

[0048] 2. The self-carbonized recycled aggregate concrete prepared in this embodiment was tested for pore size distribution by means of a mercury intrusion instrument. The results show that the pore size distribution of the recycled aggregate concrete prepared by this method is better than that of the conventional liquid-solid carbonization treatment method. Specifically, the average pore size is significantly reduced (from 46nm to 23nm), and the total porosity is significantly reduced (from 20% to 15.8% to 17.6%), indicating that the microstructure is more compact; the pore size distribution is more uniform, and the number of tiny pores increases, which helps to improve the mechanical and durability properties of concrete.

[0049] 3. Alkali treatment removes part of the old mortar, which can further enhance the bonding force between the new cement paste and the recycled aggregate and improve the strength of the interface transition zone (ITZ). Because the alkaline solution will dissolve impurities and hydration products in part of the old mortar, increase the ion content in the pore solution, provide more active sites, and increase its chemical bonding and mechanical bite force with the new cement paste, thereby improving the overall performance of the interface transition zone. The nanoindentation test results show that the interface transition zone of the recycled aggregate concrete prepared by this method has higher hardness and elastic modulus. Compared with the traditional liquid-solid carbonization method, the microhardness of the recycled aggregate edge and I TZ1 (interface transition zone between old aggregate and old mortar) in the self-carbonized recycled aggregate concrete prepared by this method increased by 11% and 13%, respectively, and the thickness of I TZ1 remained at about 90μm. As for the thickness and average elastic modulus of ITZ2 (old aggregate and new mortar), the thinnest ITZ2 reaches 50 μm, and the average elastic modulus can reach up to 45 GPa, which are 28% and 75% lower than those of recycled concrete prepared by traditional liquid-solid carbonization method.

[0050] 4. Using NaHCO3 microcapsules as the internal carbon source of recycled aggregate concrete, in which sodium bicarbonate is wrapped by the shell, can avoid the problem of carbonization products directly crystallizing on the aggregate surface. The microcapsules gradually release the carbon source, reducing the adverse effects of the crystallization of carbonization products on the performance of recycled aggregates and the interface transition zone between recycled aggregates and new slurry. Because the direct use of sodium bicarbonate solution environment to carry out the liquid-solid carbonization process easily causes the carbonization products to crystallize on the aggregate surface, forming an uneven crystal layer, and the crystal layer will hinder the carbonization reaction deeper in the recycled aggregate, resulting in reduced carbonization efficiency. In addition, the coating effect of the microcapsule and the carbon source release rate can be flexibly adjusted, such as controlling its anti-rupture ability by adjusting the thickness of the microcapsule shell; controlling the crosslinking degree of the shell and thus controlling its stability by adjusting the amount of crosslinking agent and the crosslinking time.

[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing self-carbonized recycled aggregate concrete, characterized in that: The following steps are involved: Step S1: adding polylactic acid into ethyl acetate solvent to dissolve and mix to form a polylactic acid solution; Step S2: dispersing sodium bicarbonate powder into the polylactic acid solution under magnetic stirring, and stirring for 1 to 2 hours to make the sodium bicarbonate evenly distributed in the polylactic acid solution; Step S3: adding the polylactic acid solution containing sodium bicarbonate evenly distributed into the aqueous phase containing the surfactant, and emulsifying for 0.5 to 2 hours by high-speed stirring at 3000-10000 rpm to form an O / W emulsion; Step S4: volatilizing the solvent of the O / W emulsion under stirring to solidify the polylactic acid to form microcapsules encapsulating the sodium bicarbonate; Step S5: separating and collecting the formed sodium bicarbonate microcapsules after centrifugation, filtration and sedimentation, and then storing them after washing and drying; Step S6: uniformly mixing the sodium bicarbonate microcapsules, cement and mineral admixtures to obtain a cementitious material containing a carbon source; Step S7: providing recycled fine aggregate, with a water-cement ratio of 0.35 to 0.55 and a cementitious material containing a carbon source of 300 to 600 kg / m3, and preparing self-carbonized recycled aggregate concrete after stirring, vibrating and curing.

2. The method for preparing a self-carbonized recycled aggregate concrete according to claim 1, characterized in that ,In step S1, the concentration of the polylactic acid solution is 2-5%.

3. The method for preparing a self-carbonized recycled aggregate concrete according to claim 1, characterized in that ,In step S3, the aqueous phase contains 2% to 10% of a surfactant.

4. The method for preparing a self-carbonized recycled aggregate concrete according to claim 1, characterized in that ,In step S3, the surfactant is polyethylene glycol.

5. The method for preparing self-carbonized recycled aggregate concrete according to claim 1, characterized in that ,In step S4, when the solvent is volatilized, the solvent volatilization process is accelerated by rotary evaporation, the duration is 2 to 6 hours, and the temperature is set to 50°C.

6. The method for preparing self-carbonized recycled aggregate concrete according to claim 1, characterized in that In step S4, when the solvent is volatilized, the solvent volatilization process is accelerated by reduced pressure evaporation, the duration is 2 to 6 hours, and the temperature is set to 50°C.

7. The method for preparing self-carbonized recycled aggregate concrete according to claim 1, characterized in that , step S6 comprises: Step S61, uniformly mixing the sodium bicarbonate microcapsules with cement in an amount of 5-10 wt.% of cement for 10-15 minutes; Step S62, adding mineral admixtures and mixing to form a cementitious material containing a carbon source.

8. The method for preparing self-carbonized recycled aggregate concrete according to claim 1, characterized in that In step S7, the provided recycled fine aggregate needs to be treated with alkali in advance by soaking in a sodium hydroxide solution with a concentration of 1-2% for 0.5 to 1 hour. After soaking, the recycled fine aggregate is rinsed with a large amount of clean water to remove the residual alkali solution, and then the recycled fine aggregate is dried in the sun or in a low-temperature oven to ensure that no moisture remains.